Efficacy of admission cardiotocography in early stage of labour in predicting perinatal outcome among parturients in a tertiary health facility in Ogun State, Southwest Nigeria - Oluwole Olutola Ojo; David O Awonuga; Iyabode Olabisi Florence Dedeke; Olaide Rufus Adenaya; Adedoyin Olatunde Ade-Onojobi; Oluwaseyi Isaiah Odelola; Elizabeth Oluwakemi Grillo (Nigerian Journal of Medicine, 2022)
Background: Some fetuses will present with hypoxia at admission into the labour room and may not be able to withstand the stress of frequent and adequate uterine contractions. Admission cardiotocography (CTG) in early labour has been thought to be useful in detecting babies with such conditions therefore affording the obstetrician early intervention to prevent adverse perinatal outcome. Aim: This study aims to determine the predictive value of admission cardiotocogram in early labour in the early detection of fetal hypoxia and its adverse perinatal outcome. Patients, Materials and Methods: It was a prospective cross-sectional study among low- and high-risk pregnant women in a tertiary health institution in Abeokuta, Southwest Nigeria. Two hundred participants with singleton fetus in cephalic presentation were recruited consecutively at term in early first stage of labour and were subjected to 20 min admission CTG (ACTG). The resulting cardiotocograms were classified into reactive, suspicious or pathological and further management was based on the cardiotocogram findings. Perinatal outcomes were assessed and statistical analysis done using IBM SPSS version 20. The main outcome measures were mode of delivery and perinatal outcome using Apgar scores, neonatal pulse oximetry, and neonatal unit (NNU) admission. Results: Seventy percent of the participants were multipara, 42% were aged between 26 and 30 years. Suspicious and pathological CTGs were 9% and 1%, respectively. Operative delivery, birth asphyxia, and NNU admission of babies were more common among the non-reactive (suspicious/pathological) CTG groups compared to reactive CTG group. The test, in predicting perinatal asphyxia, has low sensitivity (42.86%) and positive predictive values (15%) but high specificity (91.19%) and negative predictive values (97.78) Conclusion: ACTG is a simple, noninvasive screening tool in labour. It is highly effective in predicting fetuses unlikely to develop birth asphyxia but not so effective at predicting those likely to develop asphyxia. The test should be used with caution.